2017
DOI: 10.1007/s00464-017-5555-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery for choledocholithiasis concomitant with calculus of the left intrahepatic duct or abdominal adhesions

Abstract: LCBDH can obviously improve recovery and shorten the hospitalization period. Further, LCBDE is safe and feasible for patients of choledocholithiasis with mild and moderate abdominal adhesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In general surgeries, abdominal adhesions form surgery procedures may affect the surgical outcomes. [ 5 ] It is difficult and dangerous for patients with postoperative adhesions to gain a safe access to the peritoneal cavity by using a Veress blindly. [ 6 ] Also, it may be impossible to place trocars in the appropriate locations.…”
Section: Introductionmentioning
confidence: 99%
“…In general surgeries, abdominal adhesions form surgery procedures may affect the surgical outcomes. [ 5 ] It is difficult and dangerous for patients with postoperative adhesions to gain a safe access to the peritoneal cavity by using a Veress blindly. [ 6 ] Also, it may be impossible to place trocars in the appropriate locations.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, with the development of laparoscopic techniques and technological advances in equipment, a growing number of reports have suggested that laparoscopic procedures can also be performed as a standard treatment in patients with a history of abdominal operations [10,11]. However, there are very few reports about laparoscopic procedures in patients with a history of abdominal biliary tract surgery.…”
mentioning
confidence: 99%
“…2 Treatment methods for intrahepatic stones include peroral cholangioscopy (POCS), percutaneous transhepatic cholangioscopic lithotomy (PTCS-L), biliary duct exploration and lithotomy, and hepatectomy. [2][3][4][5] POCS and PTCS-L are only suitable for a part of patients with no liver atrophy, and with no or only mild biliary strictures. For patients with moderate to severe biliary stricture, the failure rate of POCS or PTCS-L treatment is high, and the rate of residual stones and recurrent stones is also high.…”
mentioning
confidence: 99%